Pendidikan Kesehatan pada Remaja Putri untuk Melakukan Pemeriksaan Payudara Sendiri (SADARI) Sebagai Deteksi Dini Kanker Payudara - Putri Diah Pemiliana (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
The threat of disease for people in the world is cancer. Breast cancer is a cancer that worries women. The Indonesian government prioritizes the management of breast cancer without neglecting the treatment of other types of cancer. One of the efforts to detect breast cancer is by doing breast self-examination (BSE). The BSE examination is most appropriate to be carried out routinely, at least once every month, to be precise on the 7-10th day after menstruation because at this time the breasts feel soft. The purpose of being aware of it regularly is to feel and get to know the curves of the breasts, so that if there is a change it can be detected immediately. Based on the problems found, the methods used in this community service activity are: 1) Counseling on breast self-examination (BSE), 2) Demonstration of BSE examination. Community service activities carried out in face-to-face events and counseling regarding Health Education Regarding Breast Self-Examination (Sadari) at SMP Paba Sampali are in accordance with the planning and are well implemented. Activities carried out face to face with the lecture method (counseling). This counseling will be held on Saturday, November 20 th from 15.00 to 16.00 WIB. There were 23 participants in the activity.. The results of the implementation of the activity showed that 70% of the participants were correct in answering the pre-test questions distributed. While the results of the post test showed an increase to 90% of participants answered correctly, so it can be concluded that this activity was successfully carried out.